Modeling the mediating effects of job satisfaction and organizational commitment on the relationship between internal marketing and market orientation: A study among banks employees in the republic of Yemen / Waddah Ismail Thabet Ali - Thabet Ali, Waddah Ismail (Institute of Graduate Studies, UiTM, 2018)
Empirical evidence and statistical data showed that the banking industry in Yemen suffers from weaknesses related to internal marketing, job satisfaction, organizational commitment and market orientation. Such evidence also highlighted a gap between theory and practice in the internal marketing literature - despite many studies done on the concept of internal marketing, focus has been primarily limited to internal marketing model with the three dimensions namely, visions, development and rewards. Added to this, scholars that used internal marketing concepts with five or eleven dimensions excluded the extra dimensions like empowerment and internal communications because of low factor loadings. Furthermore, a study has yet to combine job satisfaction and organizational commitment as multiple mediators of the relationship between internal marketing and market orientation. In this study, the underpinning theories employed are the social exchange theory and the equity theory and they constituted the theoretical background of this study. This study aimed to validate and propose measurement models, validate and propose a full structural model of internal marketing influence in the market orientation, and estimate the influence of job satisfaction and organizational commitment as mediating factors. This study employed correlational survey as the study method, where a total of 407 cases were used…